LA SOBERANIA EN LA CULTURA POLITICO-JURIDICA MEDIEVAL: IMAGENES Y TEORIAS - Costa, Pietro (Res Publica. Revista de Historia de las Ideas Políticas, 2023)
The medieval discourse on sovereignty is formulated around a hierarchical order of differentiated powers, at the apex of which is the kingjudge, who does not hold a position of absolute dominance, but rather functions as the culmination of a system (pointing to a pre-existing state of affairs) characterised by graduality. Conflict arises when to the model based on the emperor’s iurisdictio plenissima (removed from any superior control or judgement) is added a new discourse which is analogous to it, but which identifies the supreme apex with the Pope’s plenitudo potestatis.
Keywords: Sovereignty; hierarchical order; king-judge; iurisdictio plenissima; plenitudo potestatis